STUDENTS’ SELF-EFFICACY IN CONFRONTING CHANGES OF THE FORM ON THE FINAL PROJECT DURING COVID-19 PANDEMIC - Maulidiyah, Eka Cahya; Rohman, Khabibur (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Among changes that occur in education, especially in universities, COVID-19 pandemic affects on the change of form on final project as a requirementfor student graduation. Some universities no longer require students to writethick and complex thesis as a graduation requirement, but they switch to writearticles published in scientific journals. By then, the present study aims to seehow is the self-efficacy of final year students in responding to the policy. Thisstudy implements quantitative descriptive research design. The researchersmeasure the student self-efficacy using a scale adapted from academic self-efficacy consisting of 23 items. The results showed that final year students werenot familiar enough with reading and writing scientific articles. As many as50.98% of respondents admitted that they rarely read scientific articles. Therewere even 29.41% of respondents who had never written scientific papersbefore. Interestingly, the average score of students